Kidneys from donors after cardiac death provide survival benefit. - Snoeijs, MG; Schaubel, D; Hené, R; Hoitsma, A; Idu, M; Ijzermans, J; Ploeg, R; Ringers, J; Christiaans, M; Buurman, W; van Heurn, L (2010)
The continuing shortage of kidneys for transplantation requires major efforts to expand the donor pool. Donation after cardiac death (DCD) increases the number of available kidneys, but it is unknown whether patients who receive a DCD kidney live longer than patients who remain on dialysis and wait for a conventional kidney from a brain-dead donor (DBD). This observational cohort study included all 2575 patients who were registered on the Dutch waiting list for a first kidney transplant between January 1, 1999, and December 31, 2004. From listing until the earliest of death, living-donor kidney transplantation, or December 31, 2005, 459 patients received a DCD transplant and 680 patients received a DBD transplant. Graft failure during the first 3 months after transplantation was twice as likely for DCD kidneys than DBD kidneys (12 versus 6.3%; P=0.001). Standard-criteria DCD transplantation associated with a 56% reduced risk for mortality (hazard ratio 0.44; 95% confidence interval 0.24 to 0.80) compared with continuing on dialysis and awaiting a standard-criteria DBD kidney. This reduction in mortality translates into 2.4-month additional expected lifetime during the first 4 years after transplantation for recipients of DCD kidneys compared with patients who await a DBD kidney. In summary, standard-criteria DCD kidney transplantation associates with increased survival of patients who have ESRD and are on the transplant waiting list.